Experimental studies on engine performance and emission characteristics using castor biodiesel as fuel in CI engine. (February 2019) - Arunkumar, M.; Kannan, M.; Murali, G.
Abstract: The petroleum fuels need a constraining research for another energy source as the diminish of diesel fuels and causes of health problems. This paper studies the castor biodiesel as another source of fuel for already having CI engines with the application of new biodiesel which having new fuel properties. The study explains the utilization of castor biodiesel as another fuel for the diesel, and it may considerably weaken the exhalation of greenhouse gases as well as strengthen the castor seed production which gives employment to farmers on the city or town sides. The study reveals that the usability of castor biodiesel as another source of fuel reduces carbon monoxide to 9% correlated to diesel HC reduced by 8.8% also a considerable reduction in oxides of nitrogen. Here there was increased in SFC by 4% and the thermal efficiency reduced by 2.2%. But the environmental issues and the employment for farmers and increase their production of castor plant prefers the castor biodiesel is another source of fuel for the automobiles, cultivation and power production sectors. Highlights: Environmental defects caused by Fossil fuel. Biodiesel Production method. Produces the employment and protects the cultivating. Performance and emission studies of diesel and biodiesel. Characterization and test fuel blends.